A Corpus Based Study on Malaysian ESL Learners’ Use of Phrasal Verbs in Narrative Compositions - Akbari, Omid (2009)
The research investigated the use of phrasal verbs in two written tasks by Malaysian ESL learners. The data of the research was obtained from the EMAS (The English Language of Malaysian School Students) Corpus. The aim of the study was: (1) to investigate the distribution of phrasal verbs used in the students‟ writing, (2) to identify the types of phrasal verbs used, (3) to establish if the phrasal verbs used were accurate syntactically and semantically, and (4) to determine if any avoidance behaviour and simplification features were employed in relation to the use of phrasal verbs. The research design comprised a qualitative technique through discourse analysis supplemented with some descriptive statistics using the software Mono Conc Pro 2.2 (Barlow, 2003). The findings of the study showed that the total instances of frequency counts for all phrasal verbs used at Form 1 level were 309 compared to 677 instances at Form 4 level. This is an indicator that the students at the higher level were more capable of using phrasal verbs. Using Celce-Murcia and Larsen Freeman‟s (1999) classification of phrasal verbs (literal, aspectual, and idiomatic), it was found that idiomatic phrasal verbs were more difficult than the other types at both student levels. It was also seen that the most inaccurate phrasal verb structures at both Form 1 and Form 4 levels were in the tense form. The findings also showed that there was a highly positive progression in the number of phrasal verbs used semantically accurate. In fact, out of a total of 309 instances of phrasal verbs used at the Form 1 level, 92% were semantically accurate and 8% are inaccurate. Also, of 677 instances of phrasal verbs used at the Form 4 level, 95% were semantically accurate and 5% were inaccurate. The findings also showed that ESL learners had adopted ways to overcome their inadequacy in the use of phrasal verbs of the English language by using avoidance behaviour, simplification features and compensation strategies. In fact, since the total number of avoided phrasal verbs at the Form 4 level was less than that of the Form 1 level, it indicated that the proficiency level was an affecting factor in avoiding different types of phrasal verbs in the students‟ writing. In order to prevent the problems identified in the study regarding phrasal verb structures, and to further improve the teaching and learning of phrasal verbs among ESL learners, some recommendations are proposed.